A Long Time History of a Mediastinal Fibrosis with Triple Vascular Stenosis - Peretti, Laura; Vaillant, Pierre; Billon, Yves; Menard, Olivier; Tiotiu, Angelica (Current Respiratory Medicine Reviews, 2018)
Mediastinal fibrosis is a rare disease of diverse etiologies, but sometimes idiopathic. Its evolution is progressive and its complications depend on the structures it compresses. Vascular compressions may lead to superior vena cava syndrome, and pulmonary hypertension. Surgery and endovascular treatment may be effective, but often need to be repeated. Systemic treatments, including corticosteroids, have variable responses. We present an original case of mediastinal fibrosis, compressing the superior vena cava, the right pulmonary artery, and upper right pulmonary vein. For a 6 year follow up, the patient did not present pulmonary hypertension but only superior vena cava syndrome which was effectively treated by endovascular stenting. Systemic corticosteroids were not very effective for the improvement of symptoms. Later, the patient was treated with chemotherapy and immunosuppressive drugs for acute myeloid leukaemia. His respiratory, cardiovascular and imaging exams revealed stability which led us to reflect on the possible impact of the immunosuppressive therapy on the evolution of this mediastinal fibrosis.
Keywords: Endovascular stenting